A study of library consultancy in the Philippines - Mondonedo, Linda L.; Buenviaje, Rufo Q. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1990)
This is a study of the activities of some fifty initially identified practicing library consultants. Thru a questionnaire survey, thirty-four answered the questionnaires, while the rest, were either not practicing or did not consider themselves as consultants. The questionnaires were followed up by personal interviews before the data were analyzed.
The study revealed that thirty-one of the thirty-four library consultants were employed full time elsewhere. They occupied top positions in libraries or library schools and could do only part-time consultancy. Four were retired and also did part-time consultancy. All but four were active library consultants for 6-27 years at the time of the survey. All are bachelor degree holders; majority (97 percent) have masteral degree, 39 percent of them earned it in the United States. Seventy-nine percent of the consultants did advanced studies in information science and other related subjects. Majority were members of two or more library associations and served as its officers including the presidency.
To determine the library consultancy needs, one hundred of the top one thousand business firms in the Securities and Exchange Commission (SEC) listing were surveyed and seventy-seven responded. Thirty-seven answered the questionnaires prepared for them; forty communicated by telephone that they had no libraries; did not plan on establishing any, and therefore saw no point in answering the survey questions.
The study also revealed that of the thirty-seven business firms surveyed, twenty-three (62 percent) maintained a library. Eleven (30 percent) employed one or more full-time professional librarians and twelve (32.40 percent) hired part-time librarians.
Majority (87 percent) of these businesses provide information to their employees and these were ordinarily housed and maintained in the library. Those without libraries kept them in various departments like training department, secretaries or the president's office. Sixty-two percent think there is a need to organize the materials located in various departments or offices into a library. However, more than half (54 percent) of the respondents do not feel the need for professional services of a librarian or consultants.
From all indications, library consultancy, although practiced for twenty-seven years in the Philippines is not operated on a professional basis; and it seems that the business world is not aware of the vital service it can render to them.
The study recommends that the consultants who are well-placed in the library profession, initiate measures towards the establishment of reputable and credible consultancy services. Library consultancy looms as a vital component of alternative librarianship. The immediate establishment of an association of library consultants is strongly recommended.
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Library consultants